Optimisasi Katekese Digital: Pemberdayaan Mahasiswa Katekis dalam Evangelisasi Baru - Emmeria Tarihoran; Antonius Denny Firmato (Jurnal Penelitian Pendidikan Agama Katolik, 2024)
This research explores efforts to empower Catechist students in facing the challenges of the digital age, focusing on developing blessing skills through a digital catechesis approach. This study used qualitative methods and phenomenological approaches to involve Catechist students as the main participants. The program "Empowering Catechist Students for New Evangelization" is designed to enhance Catechist students' understanding of blessing skills, especially in the use of digital media. After engaging in the program, the results showed a significant change in the catechist students' understanding of blessing skills. Specialized training and hands-on practice with digital catechesis have had a positive impact, enabling Catechist students to be more effective in conveying the message of evangelization. This improvement in skills has also been found to contribute to the courage of Catechist students in facing communication challenges in the digital age. The conclusion of this study provides a foundation for a deeper understanding of the importance of developing blessing skills in dealing with changing contexts of religious communication. The practical implications involve improving the blessing skills training program and adjusting the catechesis curriculum to facilitate the adaptation of Catechist students to the evolving digital environment. As a result, Catechists are expected to be more effective and relevant in carrying out the mission of evangelization in this digital era.